The Future of Alternative Treatment for Substance Abusers among Secondary School Students - Moses Adeleke Adeoye; Windari Sabela (Suluh: Jurnal Bimbingan dan Konseling, 2025)
Background: Substance abuse among secondary school students is a growing concern, and conventional treatment methods such as counselling, rehabilitation, and support groups have shown limited success due to stigma, restricted access to treatment facilities, and high relapse rates. These shortcomings highlight the urgent need to explore innovative and holistic interventions tailored to adolescents’ unique developmental needs. Aim: The purpose of this research is to examine the effectiveness and future potential of alternative treatments—including mindfulness-based interventions, art therapy, and outdoor experiential programs—in addressing substance abuse among secondary school students. Method: This study adopted a qualitative research design that combined a literature review, expert interviews, case studies, and analysis of institutional programs. Data were examined thematically, focusing on patterns of treatment outcomes, barriers to implementation, and the role of school and community environments in supporting recovery. Results and Discussion: The findings reveal that mindfulness-based interventions enhance emotional regulation, reduce stress, and lower substance use tendencies; art therapy facilitates self-expression, identity formation, and coping mechanisms; and outdoor experiential programs foster resilience, teamwork, and problem-solving skills. These approaches not only mitigate the limitations of traditional methods but also provide personalised, non-stigmatising, and engaging support mechanisms for adolescents. Effective adoption requires systemic integration into school curricula, professional training for staff, and collaboration among educators, mental health practitioners, and community stakeholders. Conclusion: The study concludes that the future of alternative treatment for secondary school students struggling with substance abuse lies in the integration of evidence-based alternative therapies alongside traditional interventions. By addressing stigma and accessibility barriers while promoting holistic well-being, schools can create supportive environments that empower students to recover from substance abuse and achieve both academic and personal growth.